1991
DOI: 10.1073/pnas.88.2.340
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a cDNA encoding a second putative prohormone convertase related to PC2 in AtT20 cells and islets of Langerhans.

Abstract: PC2 and furin are two recently identified members of a class of mammalian proteins homologous to the yeast precursor processing protease kex2 and the bacterial subtilisins. We have used the polymerase chain reaction to identify and clone a cDNA (PC3) from the mouse AtT20 anterior pituitary cell line that represents an additional member of this growing family of mammalian proteases. PC3 encodes a 753-residue protein that begins with a signal peptide and contains a 292-residue domain closely related to the catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
211
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(215 citation statements)
references
References 39 publications
4
211
0
Order By: Relevance
“…Recently, the coding sequences for a number of vertebrate processing enzymes were reported, i.e. furin [3][4][5], PCI/PC3 [6][7][8][9], PC2 [7,10,11], and PC4 [12]. Furin has been shown to correctly process several precursor proteins, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the coding sequences for a number of vertebrate processing enzymes were reported, i.e. furin [3][4][5], PCI/PC3 [6][7][8][9], PC2 [7,10,11], and PC4 [12]. Furin has been shown to correctly process several precursor proteins, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The cloning of prohormone convertase 1 (PC1) (14,15), also known as PC3, a member of the subtilisin family of enzymes, has identified another candidate. PC1 is a Ca 2ϩ -dependent serine endoprotease known to cleave propeptides at dibasic residues (16,17), and there is increasing evidence that it can also cleave at mono-arginyl sites as well (18,19).…”
mentioning
confidence: 99%
“…The discovery of kexin, an endoprotease that performs such functions in May 23, 1994: revised Aug. 24, 1994accepted Sept. 6, 1994 yeast, lead to the identification of its mammalian homologs (Seidah, 1991). So far, six subtilisin/kexin-like mammalian prohormone convertases have been characterized and named furin (Roebroek et al, 1986;Van de Ven et al, 1990;or PACE, Barr et al, 1991) PC1 (Seidah et al, 1990(Seidah et al, , 1991b; also named PC3, Smeekens et al, 1991), PC2 (Seidah et al, 1990;Smeekens arid Steiner, 1990), PC4 (Nakayama et al, 1992; PACE4 (Kiefer et al, 1991), and PC5 (Lusson et al, 1993; also named PC6, Nakagawa et al, 1993a). Previous studies showed the ubiquitous distribution of furin mRNA in the CNS encompassing both neuronal and glial cells, whereas PC1 and PC2 mRNAs are restricted to neurons and endocrine cells (Seidah et al, 1990(Seidah et al, , 1991Day et al, 1992Day et al, , 1993Schafer et al, 1993).…”
mentioning
confidence: 99%